SOCIALIZATION AND PERSONAL COMPETENCIES IN THE CONTEXT OF SUCCESSFUL INTERCULTURAL COMMUNICATION - Alinder-Ismailova, D. Ergidzhan (Revista Inclusiones, 2021)
The paper discusses the problems of the intercultural education environment as socially justified. The individual develops his/her personality by interacting with other people. This is a very complex and multi-layered process where relations between people are enhanced by the inner necessity for collaboration and empathy. The process itself involves exchange of meanings, development of a unified strategy for interaction, perception and understanding of the other/the stranger that is so far away. The social sense of the intercultural education area reveals in its ability to relay forms of cultural and social experience. The sense of "equality" makes the pressure of suppression and restriction of significant personality identifications lesser. The intercultural education area presupposes both understanding of the complex and multi-dimensional personality/background identity that marks the social development of the individual and tolerance to diversity available in various (co-)identifications.